The Application of The Teaching Contextual Learning (CTL) to Increase The Motivation to Study Primary School Student - Zahrah, Riza Fatimah; Suryana, Yusuf; Enok, Enok (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The background of research is research results in 2013 that motivation students in resolving word problems mathematics was weak . The purpose of this study is to find a the motivation to study students in resolving word problems mathematics by applying contextual teaching learning ( CTL ). This research was conducted at a grade school in Kuningan districts .The methodology is descriptive , with the quantitative approach and design research used is non-equivalent control group design .This research result indicates the 75 % attention , relevance 71.43 % , confidence 72.22 % and satisfaction 80.07 % that averaged the motivation to study students were % 74.68 .The motivation to study can rise as strategy applied is learning in kinds style, assigned tasks age related and interest, and the emergence of learning community